Racial Mislabeling in Multiracial Individuals: Implications for Professional Counseling and Education - C. Peeper McDonald; Catharina Y Chang Ph.D.; Caroline O'Hara; Kan Guvensel; Lindy Parker (Teaching and Supervision in Counseling, 2020)
With the extreme growth of people who identify as Biracial or Multiracial, it is evident that their unique racial experiences need to be better understood, especially within the field of professional counseling to underscore competent practice (Charmaraman, Woo, Quach, & Erkut, 2014; Jackson, Yoo, Guevarra & Harrington, 2012; Tran, Miyake, Martinez-Morales, & Csizmadia, 2016). As a result, the researchers in this study investigated the lived experiences of racial mislabeling for Multiracial individuals. The participants of this study were fourteen (n=14) individuals who identified as Multiracial and endorsed experiencing the specific form of racial invalidation entitled racial mislabeling. Data were collected through individual, semi-structured interviews. The data was analyzed using phenomenological methods within Moustakas’ (1994) transcendental approach, which led to themes that described the essence of the participants’ experience. These themes are discussed in detail and recommendations for researchers and counselor educators to improve training and education are provided.
Keywords: Professional Counselors; Racial Mislabeling; Counselor Education